Pengaruh Minat Belajar Terhadap Pemahaman Konsep Matematika Pada Materi SPLDV Kelas X SMK Al-Falah Jakarta Selatan - Ahmad Fikri (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This research explores the important role of learning interest in increasing students' understanding of mathematical concepts, especially on the topic of Systems of Linear Equations in Two Variables (SPLDV). Using a quantitative approach and correlational survey method, this research analyzes the relationship between students' learning interest and their understanding of concepts. Data was collected from 94 grade 10 students at Al Falah Vocational School, South Jakarta. The research results show that students who have a high interest in learning have better understanding, with a correlation coefficient of 0.70 and a determination coefficient of 49%. These results show that almost half of the variation in students' SPLDV understanding can be explained by their learning interest. This research also emphasizes the need for innovative teaching methods to increase student engagement and understanding. Implications for educational strategies and future research directions are discussed.